Stromal Tumors in the Prostate - Aspitri ani; Kurniawan Dedy (Jurnal RSMH Palembang, 2020)
Stromal tumors of the prostate are rare mesenchymal tumors of the prostate stroma,in the form of spindle cell tumors, which are differentiated by cellularity, mitotic index,cellular atypia, and necrosis. These tumors are classified into two; prostatic stromaltumors of uncertain malignant potential (STUMP) and prostatic stromal sarcomas (PSS).The incidence is about 0.1-0.2% of the total incidence of prostate cancer. Thepathogenesis of prostate stromal tumors is based on origin, clonal and chromosomalabnormalities. Clinical symptoms of complaints lead to lower urinary tract obstruction,dysuria and pollakiuria as well as abnormalities in the rectal toucher (RT) examination.Macroscopically, brownish-white masses were found showing a solid or solid-cysticpattern. Radiological examination can use transrectal ultrasound (TRUS), CT Scan andMRI. Histopathologically, prostate STUMP has five different patterns, namely thedegenerative atypia pattern, hypercellular stroma pattern, phyllodes-type growthpattern, myxoid pattern, and epithelioid stromal pattern. Meanwhile, in PSS, there arehistological patterns of storiform, epithelioid, fibrosarcomatous, and patternless growthpatterns. Then PSS was subclassified into two, namely low grade and high gradetumors. Immunohistochemical examination showed immunoreactivity for CD34, PR,smooth muscle actin (SMA), desmin, HHF35, smooth muscle actin, vimentin andandrogen receptors and negative for estrogen receptors, CD117 and S-100. Thedifferential diagnosis is rhabdomyosarcoma, leiomyosarcoma, inflammatorymyofibroblastic tumor, sarcomatoid carcinoma, benign prostate hyperplasia, smoothmuscle tumor, gastrointestinal stromal tumor, and solitary fibrous tumor. Prognosis ofprostate STUMP is better than that of PSS. Treatment of STUMP is currently unknown.Definitive resection can be performed taking into account the patient's age, treatmentpreference, and the size or size of the lesion. Treatment for PSS radical prostatectomy,cystoprostatectomy, or pelvic exenteration for local aggressive tumors.